Strengthening Chronic Disease Management in Ontario - McMaster Health Forum (My University, 2009)
Video interviews with participants in a stakeholder dialogue about Strengthening Chronic Disease Management in Ontario (on YouTube).
http://www.youtube.com/playlist?list=PL3AE50C3A65D0A0F4&feature=plcp
Keywords: disease; management; Ontario